A role for p21‐activated kinase 7 in the development of gastric cancer. (23rd November 2012) - Gu, Jun; Li, Keqiang; Li, Maolan; Wu, Xiangsong; Zhang, Lin; Ding, Qichen; Wu, Wenguang; Yang, Jiahua; Mu, Jiasheng; Wen, Hao; Ding, Qian; Lu, Jianhua; et al.
<x xml:space="preserve">Abstract</x> p21‐activated kinase (PAK)7 (also known as PAK5) is a member of the group B PAK family of serine/threonine protein kinases, which are effectors of the small GTPases Rac and CDC42. PAK7 can promote neurite outgrowth, induce microtubule stabilization, and activate cell survival signaling pathways. However, the role of PAK7 in cancer is still poorly understood. Here, we showed that PAK7 expression was upregulated in different gastric cancer cell lines and gastric cancer tissues, as compared with human embryonic kidney 293 cells and adjacent normal tissues, respectively. The results suggested that PAK7 expression was related to gastric cancer progression. Thus, we employed lentivirus‐mediated small interfering RNA to inhibit PAK7 expression, to investigate the role of PAK7 in human gastric carcinogenesis. RNA interference efficiently downregulated expression of PAK7 in SGC‐7901 and MGC‐803 cells at both mRNA and protein levels. Knockdown of PAK7 inhibited human gastric cancer cell proliferation by inducing cell cycle arrest in G0/G1 phase, in concordance with the downregulation of CDK2, CDC25A, and cyclin D1. Our data suggest that PAK7 is a new hallmark of gastric cancer, in which PAK7 might contribute to gain of tumor growth potential, acting by affecting the expression of cell cycle regulators. Therefore, PAK7 may be an attractive candidate as a therapeutic target in gastric cancer.